Respon Pupuk Fosfat dan Silika Terhadap Pertumbuhan Padi Hitam (Oryza sativa L. Indica) - Amran Jaenudin; Iman Sungkawa; Nengsih Nengsih; Maryuliyanna Maryuliyanna (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Black rice produces black rice which contains a lot of nutrients for the body, but there is still not much research done in increasing the growth and productivity of black rice. The purpose of this study was to determine the level of increase in the productivity of black rice after the addition of phosphorus and silica fertilizers to black rice varieties. The experimental location is in Palir Village, Tengah Tani District, Cirebon Regency with a height of four 9 m above sea level. The type of soil in the experimental location was alluvial with a pH of 6. The experiment was carried out in March-August 2019. This experiment used a factorial RAK consisting of SP36 (P) fertilizer dosage and SipadiHS (S) Silica fertilizer dosage. The dosage of SP36 (P) fertilizer consists of P1 (50 kg ha-1) P2 (100 kg ha-1) and P3 (150 kg ha-1) while the dosage of SipadiHS (S) silica fertilizer consists of S0 (without silica), S1 (100 kg ha-1), S2 (200 kg ha-1) and S3 (200 kg ha-1). The results showed that there was an interaction with the variable height growth of plants aged 56 DAS in P2S3 and P3S3 treatments and the number of tillers 56 DAS in P2S1 treatment. Meanwhile, phosphate and silica treatments independently affected the observations of plant height at the age of 28 DAS and 42 DAS, Shoot Root Ratio at 42 DAS and 56 DAS. Keywords: black rice, SP36, Silica SipadiHS